간호대학생의 간호전문직관, 돌봄효능감 및 윤리적 민감성이 돌봄행위에 미치는 영향 - 진수희; Su Hee Jin; 김은희; Eun Hee Kim (보건정보통계학회지, 2020)
Objectives: It is important for nursing students to properly establish the caring behaviors awareness in order to become a competent and professional nurse in the future. This study was to examine the effects of nursing professionalism, caring efficacy, and ethical sensitivity on caring behaviors in nursing students. Methods: The subjects of this study were total 205 nursing students in universities located in D Metropolitan City. Data were collected from September 2 to 30 in 2019 by using self-reported questionnaires. The data were analyzed by using statistical package the independent t-test, one-way ANOVA, Pearson’s correlation coefficients, and stepwise multiple regression analysis with IBM SPSS 25.0 program. Results: The mean score of ethical sensitivity was 4.40±0.42, caring efficacy was 3.69±0.33, nursing professionalism was 3.57±0.40, and caring behaviors was 4.04±0.49. There were significant differences in biomedical ethics awareness by grade and satisfaction of nursing major. The influencing factors on caring behaviors in nursing students were ethical sensitivity (β=0.44, p<0.001), nursing professionalism (β=0.18, p=0.005), grade (β=0.18, p=0.006), and caring efficacy (β=0.16, p=0.006) which explained 31.1% of the variance. Conclusions: These results highlight the importance of developing caring behaviors in nursing students and the need to develop intervention programs that can enhance their nursing professionalism, caring efficacy, and ethical sensitivity should be considered.